Effect of time on recovery of plasma microsamples for the quantitative determination of vancomycin. (November 2016) - Parker, Suzanne L; Guerra Valero, Yarmarly C; Lipman, Jeffrey; Roberts, Jason A; Wallis, Steven C
The reliability of extraction recovery of an analyte in bioanalysis is fundamentally important for downstream analytical testing. For dried format microsamples, if the recovery changes with time the concentration in clinical samples, derived from calibration standards and alongside quality control samples prepared following different drying protocols, may not reflect the true result. The purpose of this paper was therefore to evaluate changes to extraction recovery across time for one analyte, the glycopeptide antibiotic vancomycin, in plasma using two dried microsampling formats, dried plasma spots and volumetric absorptive microsampling.